ANALISIS KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKALONGAN - Septiana, Niniek; Suwitri, Sri; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Department of Population and Civil Registration Pekalongan are the providers of public services in the field of population administration for all citizens Pekalongan, where the quality of service that is still found complaints and problems. This research is a qualitative descriptive study, which aims to describe the quality of service in the Department of Population and Civil Registration Pekalongan. Informants in this study include: Head of the Department of Population and Civil Registration Pekalongan, front-line service personnel and people who are doing ministry in the service of population and civil registration Pekalongan city. The results showed that the quality of service in the Department of Population and Civil Registration Pekalongan are still not optimal, visible from several phenomena research service quality there are still some shortcomings., Namely: the slow completion of service, kuarnganya facilities and infrastructure, the lack of assurance of security. But to requirements, procedures, costs and product services in compliance with existing standards. For reliability and empathy dimension has been met, but for aesthetics, assurance and responsiveness yet. Based on these results it is suggested for population and civil registration offices Pekalongan city in improving the quality of service is: necessary additional staff, provision of security guard services and the renovation of the building and the addition of service infrastructure.